A Bibliometric Analysis of Romanian Leading Journals in Economics - Claudiu CICEA; Corina MARINESCU; Nicolae PINTILIE (Communications of International Proceedings, 2021)
The aim of this paper is to analyse the published scientific content of two leading journals from Romania and the only ones from the Bucharest University of Economic Studies, indexed by Web of Science database, belonging to the Economics category, in order to reveal specific features related to trends, topics and impact of published articles. The leading journals are: Amfiteatru Economic (AMF) and Economic Computation and Economic Cybernetics Studies and Research (EcoCyb). For this reason, a bibliometric study is developed. In this regard, the authors synthesized within the literature review section, some previous studies focusing on bibliometric analysis. Afterwards, the research methodology is presented and applied in order to provide results of the bibliometric analysis. Among them, one can briefly state that: the highest number of contributions (published papers) belongs to a Romanian author for AMF and to a Lithuanian author for EcoCyb; the most cited article was recently published in EcoCyb and rapidly gained visibility and a high number of citations; the most frequent keywords in articles published by AMF are sustainability, sustainable development and Romania, while for Ecocyb, they are: Romania, economic growth and forecasting; more powerful link strength for keywords from articles belonging to AMF; a higher number of topics (and evenly distributed in time) was identified for AMF as compared to EcoCyb.
Keywords: Bibliometric Analysis; Citation Analysis; Keywords; Topics; Trends.